ANALISIS KUANTITATIF Fe DAN Mn DALAM AIR SUMUR MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Ngibad, Khoirul (CHEDS: Journal of Chemistry, Education, and Science, 2023)
Fe and Mn metal are two types of an environmental pollutant that is usually found in water. The danger of Fe and Mn metals in groundwater is that they can cause poisoning, intestinal damage, and chronic diseases in humans. The study aimed to measure the levels of Fe and Mn in well water in Taman District, Sidoarjo Regency. Fe and Mn levels were determined using the AAS method with a wavelength of 248.3 nm for Fe and 279.5 nm for Mn. The levels of Fe and Mn in well A water samples were 0.08 and 0.08 mg/L, respectively, while the Fe and Mn levels in well B water samples were 0.019 and 0.14 mg/L, respectively. Thus, the well water samples still meet the quality standards (maximum levels) for the chemical parameters of Fe and Mn in the environmental health quality standards.